Modulation of interleukin‐36 based inflammatory feedback loop through the hepatocyte‐derived IL‐36R‐P2X7R axis improves steatosis in alcoholic steatohepatitis. (22nd May 2022) - Shang, Yue; Yang, Hong‐Xu; Li, Xia; Zhang, Yu; Chen, Nan; Jiang, Xue‐Li; Zhang, Zhi‐Hong; Zuo, Rong‐Mei; Wang, Hui; Lan, Xiao‐Qi; Ren, Jie; Wu, Yan‐Ling; et al.
Abstract : Background and Purpose: Interleukin‐36 is induced by proinflammatory cytokines and promotes inflammatory responses, creating an IL‐36‐based inflammation loop. Although hepatocytes, produce IL‐36 responses to drug‐induced liver injury, little is known about the mechanistic role of IL‐36 signalling during the progression of alcoholic steatohepatitis (ASH). Regarding IL‐36/IL‐36R and P2X7R coregulating the inflammatory response, we elucidated that modulation of IL‐36R‐P2X7R‐TLR axis affected hepatocyte steatosis as well as the IL‐36‐based inflammatory feedback loop that accompanies the onset of ASH. Experimental Approach: C57BL/6J mice were subjected to either chronic‐plus‐binge ethanol feeding or acute gavage with multiple doses of ethanol to establish ASH, followed by pharmacological inhibition or genetic silencing of IL‐36R and P2X7R. AML12 cells or mouse primary hepatocytes were stimulated with alcohol, LPS plus ATP or Poly(I:C) plus ATP, followed by silencing of IL‐36γ, IL‐36R or P2X7R. Key Results: P2X7R and IL‐36R deficiency blocked the inflammatory loop, specifically initiated by IL‐36 cytokines, in hepatocytes of mice suffering from ASH. Pharmacological inhibition to P2X7R or IL‐36R alleviated lipid accumulation and inflammatory response in ASH. IL‐36R was indispensable for P2X7R modulated NLRP3 inflammasome activation in ASH, and IL‐36 led to a vicious cycle of P2X7R‐driven inflammation in alcohol‐treated hepatocytes. TLR ligands promoted IL‐36γ production in hepatocytes, based on synergism with P2X7R. Conclusions and Implications: Blockade of IL‐36 based inflammatory feedback loop, via IL‐36R‐P2X7R‐TLRs‐modulated NLRP3 inflammasome activation, circumvented steatosis and inflammation that accompanies the onset of ASH, suggesting that targeting IL‐36 can serve as a novel therapeutic approach to combat ASH. Abstract :